Studies of Olfactory System Neural Plasticity: The Contribution of the Unilateral Naris Occlusion Technique. (28th May 2012) - Coppola, David M.
Abstract : Unilateral naris occlusion has long been the method of choice for effecting stimulus deprivation in studies of olfactory plasticity. A significant body of literature speaks to the myriad consequences of this manipulation on the ipsilateral olfactory pathway. Early experiments emphasized naris occlusion's deleterious and age-critical effects. More recent studies have focused on life-long vulnerability, particularly on neurogenesis, and compensatory responses to deprivation. Despite the abundance of empirical data, a theoretical framework in which to understand the many sequelae of naris occlusion on olfaction has been elusive. This paper focuses on recent data, new theories, and underappreciated caveats related to the use of this technique in studies of olfactory plasticity.